Judge Schermer and the Creation of the United States Bankruptcy Appellate Panel for the Eighth Circuit - Robert J. Kressel (Washington University Journal of Law & Policy, 2017)
This Article examines the influence Judge Barry Schermer had on the then-newly created United States Bankruptcy Appellate Panel for the Eighth Circuit. Judge Kressel begins by noting the unique role the Appellate Panel has, as it has concurrent jurisdiction with the district court of appeals from the bankruptcy courts in the circuit, and not all circuits have these panels. The Author concludes Schermer’s dedication to bankruptcy law helped shape the roles of these panels, which is further suggested by Judge Schermer’s recent appointment to a fourth seven-year term in this role.
Keywords: Bankruptcy Appellate Panel; Appellate Law; Eighth Circuit; Bankruptcy Law History; Judge Schermer